2015
DOI: 10.1161/circresaha.116.303771
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Cardiovascular Health

Abstract: Sodium is an essential nutrient. Increasing sodium intake is associated with increasing blood pressure, whereas low sodium intake results in increased renin and aldosterone levels. Randomized controlled trials have reported reductions in blood pressure with reductions in sodium intake, to levels of sodium intake <1.5 g/d, and form the evidentiary basis for current population-wide guidelines recommending low sodium intake. Although low sodium intake (<2.0 g/d) has been achieved in short-term feeding clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 63 publications
4
119
0
7
Order By: Relevance
“…However, non-caloric soft drink is high in sodium, which is demonstrated in the present study by a 12% increase in total sodium intake only by the non-caloric soft drink group. High sodium intake is associated with high blood pressure and cardiovascular disease [31]. Even if non-caloric soft drinks do not contain sucrose and their association with obesity is questioned, it is suggested that its consumption be avoided due to the amount of sodium they provide.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-caloric soft drink is high in sodium, which is demonstrated in the present study by a 12% increase in total sodium intake only by the non-caloric soft drink group. High sodium intake is associated with high blood pressure and cardiovascular disease [31]. Even if non-caloric soft drinks do not contain sucrose and their association with obesity is questioned, it is suggested that its consumption be avoided due to the amount of sodium they provide.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some individuals, moderate changes (1-2 g/day) in sodium intake can exert a substantial effect on BP, a concept called salt sensitivity. A physiological consequence of low sodium intake is activation of the renin-angiotensinaldosterone system (RAAS) and catecholamine (O'Donnell, Mente, & Yusuf, 2015) Grades of hypertension Subjects in the control group (66.7%) had grade 1 hypertension with SBP mean of 156.72±10.25 and 156.22±10.70 in the intervention group with the same percentage. This study did not directly examine the awareness of subjects to hypertension, but this condition may explain the lack of awareness of subjects to an increased in BP.…”
Section: Habits Of the Subjectsmentioning
confidence: 99%
“…In their meta-analysis, Micha et al stated that processed meats contain about 400 % more sodium and 50 % more nitrates per g (47) , although this depends strongly on the type of meat and the methods used (49) . A high salt intake is thought to be associated with hypertension and, consequently, an increased risk of CVD (50,51) , although it is currently still unclear which amounts of salt intake do affect blood pressure and whether only certain subgroups of the population would particularly benefit from decreasing their salt intake (52) . Processed meats such as sausages, salami and bacon have a higher content of SFA and cholesterol than fresh red meat; the latter is often consumed after removing the visible fat tissue, whereas the proportion of fat in sausages often reaches 50 % of weight or even more.…”
Section: Cvdmentioning
confidence: 99%